Can cytomegalovirus infection affect male reproductive function? Results of a retrospective single‐centre analysis. (8th June 2020) - Cito, Gianmartin; Coccia, Maria Elisabetta; Picone, Rita; Fucci, Rossella; Micelli, Elisabetta; Cocci, Andrea; Di Mauro, Marina; Rizzello, Francesca; Giachini, Claudia; Minervini, Andrea; Carini, Marco; Natali, Alessandro
Abstract: Our objective was to investigate whether the chronic cytomegalovirus (CMV) infection can affect semen parameters in men with couple infertility and to assess the impact of male CMV infection on the reproductive outcomes of CMV‐seronegative women suffering from tubal factor. Group 1 included CMV IgG‐seropositive men, Group 2 CMV IgG‐seronegative patients. Seminal parameters, two‐pronuclear (2PN) fertilization rate (FR), 1‐2‐3PN FR, cleavage rate (CR), miscarriage rate (MR), pregnancy rate (PR) and live birth rate (LBR) were collected. Two hundred and twenty‐two men were included: 115 (51.8%) in Group 1 and 107 (48.2%) in Group 2. There was reported a low trend towards higher sperm concentration/ml, total sperm count and viability in CMV IgG‐seronegative males, compared to CMV IgG‐seropositive ( p > .05). Semen volume, pH, motility and normal sperm morphology were similar among groups. Considering the subgroup of men, partners of CMV IgG‐seronegative females, 65 couples (29.2%) were selected. Median 2PN FR was 67%, total FR 83%, CR 100%, PR/cycle 26.2%, MR 10.8%, LBR/cycle 15.4%. No significant differences were found regarding the reproductive outcomes between CMV IgG‐seropositive men and those seronegative. CMV did not seem to play a key role in male reproductive function, as well as in influencing sperm fertility potential in the assisted reproductive outcomes.